PENGARUH GAYA MENGAJAR GURU DAN MOTIVASI BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI - Riani Khuzaimah, (Pendidikan Ekonomi, 2011)
The article is intended to investigate to what extent teaching styles and the students learning motivation influence partially and simultaneously the students achievement in the accounting lesson. The study sampled 127 students out of 200 tenth-graders of office administration classes at SMK N 1 Surabaya. Data obtained from questionnaires and documentation were analyzed with multiple regression technique. The result shows that both the teachers teaching styles and students learning motivation contribute a greater influence to the students achievement. However, learning motivation has more dominant influence on the students achievement than the teachers teaching styles do.